2008
DOI: 10.1007/s00436-008-1034-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Trypanosoma cruzi II infection in Colombian chagasic patients

Abstract: Trypanosoma cruzi is genetically classified into at least two major lineages named T. cruzi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
40
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 18 publications
4
40
1
1
Order By: Relevance
“…Our results showed that using two molecular markers was not sufficient for typing of T. cruzi isolates. These limitations were also observed by other authors 32,[60][61][62][63] . However, the use of three genetic markers with different evolutionary rates was able to ensure the correct typing of T. cruzi isolates.…”
Section: Discussionsupporting
confidence: 63%
“…Our results showed that using two molecular markers was not sufficient for typing of T. cruzi isolates. These limitations were also observed by other authors 32,[60][61][62][63] . However, the use of three genetic markers with different evolutionary rates was able to ensure the correct typing of T. cruzi isolates.…”
Section: Discussionsupporting
confidence: 63%
“…In humans infected with T. cruzi, 60-70% never develop symptoms of infection, whereas the other 30-40% will develop symptoms that manifest themselves in one of at least three general ways (cardiac, digestive, or both), 1,13 and this is known to vary by region, with the southern cone of South America being associated with gastrointestinal problems and in the northern parts of South America associated with heart failure. 85 These disease variations have been linked to the different T. cruzi genotypes circulating in these areas. 5,8 T. cruzi parasitemia in mice and opossums has been found to vary with T. cruzi strain and clone, 12,86-89 tissue lesions caused by T. cruzi have been found to be different between sylvatic and domestic animals, 13 and differential tissue distribution was observed between different clones of T. cruzi when infecting mice.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the influence of the stDNA copy number difference between the T. cruzi lineages has been established (12,15,24), where the number of stDNA copies in T. cruzi I is lower than the number in T. cruzi II. It is important to mention that parasites circulating in Colombia belong to T. cruzi I but there is evidence of patients infected with T. cruzi II parasites (26,46). This fact could affect the sensitivity of the PCR due to changes in the sequence and copy number seen in the parasites according to the primers used.…”
Section: Discussionmentioning
confidence: 99%
“…This parasite can be genetically classified into two major lineages, namely, T. cruzi I, which is found in northern South American countries, and T. cruzi II, which is found in southern South American countries (46). Chagas' disease is a chronic systemic disease endemic to both South and Central America.…”
mentioning
confidence: 99%